APLIKASI PEMBELAJARAN FIQIH BERBASIS ANDROID (Information Technology and Telematics, 2014)
Abstract - In the current era was so important for the understanding of jurisprudence and Sufism life and human life, the Muslim community should we learn from an early age. So that we can know the good and bad deeds, and can find the clean and unclean, because this learning must bring the book who do not understand the meaning of the contents of the book. To understand the meaning and explanation of the contents of the book we must diligently follow the teachings of the book. Of course this still requires a lot of time and many people are reluctant to do so. Research system of jurisprudence based learning android application which is taken from the Book of Authorship Safinatun Najah Abdullah bin Salim bin Saad bin Al Hadhrami Sumair, to be used to assist users in learning and understanding of jurisprudence that are mobile. System of jurisprudence learning application is built using the Java programming language using the Android Developer Tools. As for the sqlite database used is that a package of public-domain software that provides a relational database management system, or RDBMS. The result of this research is a learning application that provides the fiqh material - material that was taken in the Book Safinatun Najah. The application comes with Islamic issues with using multiple choice answers. Keywords: Fiqih, Tasawuf, Kitab Safinatun Najah, Android.